Peran Profesionalisme Guru dalam Mengelola Kelas dengan Baik: Kunci Sukses Pembelajaran Efektif - Siti Nabila; Izzatul Aisy; Latifa Nurul Audi; Ade Irma; Rena Revita (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to describe the role of teacher professionalism in classroom management as a determining factor of effective learning. A qualitative approach was used, with data collected through interviews and observations at SMAN 2 Tambang, SMAN 1 Tambang, and SMAN 12 Pekanbaru. The findings reveal that professional teachers not only possess pedagogical competence but also demonstrate reflective attitudes, responsiveness to student needs, and the ability to create enjoyable and interactive learning environments. Professional teachers design flexible and adaptive lessons, provide constructive feedback, and routinely engage in self-evaluation. These findings highlight the importance of strengthening teacher professionalism as the foundation for meaningful and high-quality learning processes. Therefore, continuous development of teacher professional competence should be encouraged to achieve holistic educational goals.